DISKURSUS KEGILAAN DALAM NOVEL KALATIDHA KARYA SENO GUMIRA AJIDARMA - nfn Nurcholish (Balai Bahasa Provinsi Riau, 2015)
This article discusses the discourse of madness in the novel Kalatidha Seno Gumira Ajidarna. This research focused on how the construction of the discourse of madness in the text of the novel Kalatidha and how the discourse of madness in the novel destabilize the dominant thinking about the madness.. The analysis showed that the construction of the discourse of madness in the novel Kalatidha not based totally on the structure of a particular paradigm, be it in the framework of the modern paradigm and post-structural paradigm. Discourse of madness in the novel Kalatidha reveals a number of ironies and contradictions within the dominant discourse of madness, so that any construction of meaning in the text looked intact and stable.